A case report of pulmonary atresia with intact ventricular septum: an extraordinary finding of subsystemic right ventricle - Luo, Gang; Liu, Ai; Sun, Hongxiao; Wang, Kuiliang; Pan, Silin (Frontiers in Pediatrics, 2024)
Background Massive tricuspid regurgitation (TR) is the most common feature of pulmonary atresia with intact ventricular septum (PA/IVS), and the mild or absence of TR is observed in severe right ventricular (RV) dysplasia or RV-to-coronary fistulous connections, resulting in non-biventricular (BV) outcomes postnatally.Case summary We report a case of fetal severe pulmonary stenosis with IVS diagnosed at 26 gestational weeks. The severity of RV hypoplasia did not worsen and not reached indications of intrauterine intervention, while the jet velocity of TR decreased significantly during pregnancy. The fetus was definitely diagnosed as PA/IVS with mild RV dysplasia after birth.Unusual, it doesn't suffer severe TR and myocardial sinusoids, the TR jet velocity was maintained at 2.0 m/s, and coronary artery was almost normal. The incapable RV cannot pump blood to pulmonary circulation after RV decompression from valvular perforation and balloon dilation. It may be an extraordinary finding of subsystemic RV.Conclusion PA/IVS is a heterogeneous disease with various degrees of RV dysplasia. Mild or no baseline TR is a reliable indicator with non-BV outcomes for PA/IVS fetuses, even with the acceptable dysplasia RV structures.